Orthodontic Treatment Needs of 14-18 Year-Old Male Students of Isfahan (Iran) in 2009-2010 Using IOTN Index - Farzin Aslani; Fatemeh Teimouri; Saeid Sarandi; Parvin Khadem; Masoud Feyzbakhsh; Sepideh Dadgar
Introduction: The purpose of this study was to assess orthodontic treatment needs of 14-18 year-old male students of Isfahan public schools which were carried out in 2009-2010 via Index of Orthodontic Treatment Need (IOTN).Materials & Methods: The study sample comprised 408 14-18 year-old male students selected by random clustering method. The subjects were examined clinically via IOTN which has two components: Dental Health Component (DHC) and Aesthetic Component (AC). Data were analyzed by chi-square test (α=0.05). Results: Regarding DHC, 4.4% of samples had very severe need (DHC5), 16.2% had severe need (DHC4), 22.5% had moderate need (DHC3), and 56.9% had minimum or no need (DHC1, 2) to Orthodontic treatment. In those showing grade 5, the most common malocclusion was unerupted teeth (i). The most common malocclusion in grade 4 was hypodontia (h) and in grade 3 was, overjet less than 4 mm and more than 2 mm (a). The most common malocclusion in grade 2 was contact displacement (d) less than 2 and more than 1 mm. In addition, regarding AC, 76.5% of the subjects were classified as "no need", 15.2% as "borderline need" and 8.4% as "definite need" for treatment. Conclusion: 20.6% of 14-18 year-old male students in Isfahan needed orthodontic treatment (IOTN grades 4 and 5).